Ranges & Areal Proportions of Basic Functional Activities in Residential Apartment of Multi story housing projects in the city of Erbil. - Al-Sanjary, Hasan Abdulrazzaq (Sulaimani Journal for Engineering Sciences, 2017)
House built area determination has formed one of the main economical design tools in housing policies programs around the world. To ensure the efficient performance of these designs, these programs standards has linked the dwelling space determination with its distribution among residents basic functional activities in areas and proportions that efficiently perpetuate his daily life requirements. The research discusses the availability of these rules in the design of multifamily housing output in the city of Erbil , which has seen a huge revival in the field of residential construction during the past years. With the absence of binding design criteria for the design of the city's housing production, the research aims to test the designer's commitment to distribute the available apartment space between the basic functional activities areas and ratios optimized to achieve the highest compatibility with the user's needs. To achieve the goal, a group of apartments has been elected (with economic space and different capacities) from a selected three housing projects implemented in the city . an evaluation of efficiency of their basic functional activities areas & proportions distribution has been made by testing their values change with the change of the resident apartment designer, area and capacity and by comparing with the design standards provided by the general housing programme for Iraq as a best comprehensive study can be adopted for the evaluation.
Keywords: Multi-Family Housing; Housing Standards; Areal Proportions; Economical Design